The many faces of autoimmune-mediated melanocyte destruction in melanoma - Ungureanu, Loredana; Vasilovici, Alina Florentina; Halmágyi, Salomea-Ruth; Trufin, Ioana Irina; Apostu, Adina Patricia; Şenilă, Simona Corina (Frontiers in Immunology, 2024)
Melanoma is the most severe form of skin cancer with an incidence that is increasing all over the world. Melanoma cells derive from normal melanocytes and share different melanocyte-specific antigens, the same antigens against which an immune reaction develops in vitiligo, a skin disease characterized by autoimmune-mediated melanocyte destruction. The purpose of this review is to present the autoimmune-mediated melanocyte destruction associated with melanoma development, progression and treatment. Patients with vitiligo seem to have a lower chance of developing melanoma. On the other hand, patients with melanoma can develop depigmented lesions even at distant sites from the primary tumor, defined as melanoma-associated leukoderma (MAL). Drug-associated leukoderma (DAL) was also described in melanoma patients treated with immunotherapy or targeted therapy and it seems to be a favorable prognostic factor. Clinically, MAL and DAL can be diagnosed as vitiligo and there are few differences between these three entities. In this review, the incidence of DAL in melanoma patients treated with different therapies was researched in the literature and patient outcome was recorded, with studies showing a prolonged disease-free survival in melanoma patients with DAL, treated with immune checkpoint inhibitors. Further studies are however needed to understand the dynamics of autoimmune-mediated melanocyte destruction.